Inheritance of Tartib Cultural Values at the Family Level in Ciptarasa Traditional Village - Hikmat Nashrullah Latief; Rina Hermawati; Opan Suhendi Suwartapradja (Eduvest - Journal of Universal Studies, 2025)
The residents of Kampung Adat Ciptarasa, which is part of Kesatuan Adat Banten Kidul Kasepuhan Gelaralam Community, are citizens who obey customary rules which they call “Tartib” and are bound to the provisions of ancestral customs or “tatali paranti karuhun”. The purpose of this research is to describe how the adat family conduct the transmission of culture eseciallyas they callthe cultural value of Tartib. This value has the power to guide the lives of the residents of Kampoong Adat Ciptarasa. In addition, this research explains how Tartib is taught to individuals of Kasepuhan Ciptarasa in family level. The research method used is ethnographic qualitative research method with data collection techniques using semi-structured interviews and field observations. The result of this research is that Tartib can be interpreted as what is planned, and what the Kasepuhan people in Kampoong Ciptarasa have done is considered in accordance with the applicable customary procedures. The carefully attitude, is closely related to the principle of Tartib which also means obeying parents, the Baris Kolot or the ols people, to the Sesepuh Girang including the ancestors. In addition, the family has a very important role in instilling the cultural value of tartib in the lives of Kasepuhan eople in Kampoong Ciptarasa.